BILINEAR HILBERT TRANSFORM IN \(\mathcal{G}_{L^{p_1}} × \mathcal{G}_{L^{p_2}}\) - Bučkovska, Aneta (Matematichki Bilten, 2000)
Bilinear Hilbert transform in appropriate Colombeau algebras \(\mathcal{G}_{L^{p_1}} × \mathcal{G}_{L^{p_2}}\) are given. The relations of bilinear Hilbert transforms with the corresponding definitions in Colombeau algebras are given through special regularizations.